Exploring high contrast limitations for image slicer based integral field spectrographs - Salter, G; Thatte, N; Tecza, M; Clarke, F; Verinaud, C; Kasper, M; Abuter, R (2008)
Current simulation and experimental investigatory work is going on into the performance of slicer and lenslet IFS designs. The aim of this work is to determine which technology holds the best promise for achieving the highest contrasts with EPICS on the E-ELT. Results from Spectral Deconvolution methods for high contrast detections are presented, both on sky images from AB Dor C observations using SINFONI on the VLT and improvements to the algorithms made through use of EPICS simulation data. Using these simulations, only containing photon and speckle noise, we have been able to detect simulated planets down to a contrast of 1010 located less than 1" from the parent star. The effects of spectral resolution and wavelength range on high contrast observations are discussed. Shortening the wavelength range increases the inner working angle. It is seen that an outer working angle is also reached that decreases with spectral resolution. The limit on the inner working angle can be overcome partly by increasing the wavelength range of the instrument although another inner working angle limit will be reached if a coronagraph is used. The limit of the outer working angle can also be overcome by increasing the spectral resolution of the instrument or possibly by making an IFS that produces an output with a constant spectral resolution, R,instead of constant Δλ.This is still a work in progress.